THE EFFECT OF CONCEPT MAPPING STRATEGY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMA PGRI PEKANBARU IN WRITING EXPLANATION TEXT - Adwas, Mella Kepriyanti; Aruan, Rumiri; Novitri, Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research was aimed to find out wheteher there is an effect of concept mapping strategy on the ability of the second year students of SMA PGRI Pekanbaru in writing explanation text. In conducting the research, pre- experimental research with one group pre-test post- test design was used. The sample of this research was the students of class XI IPA II which consist of 22 students. The pre- test was administered before the treatment. After the treatment was applied for five meetings using concept mapping strategy, the post test was administered. The data were analyzed using t-test formula. From the calculation, the writer found that the value of t-test was 22.363 while the t-table was 2.079. Since the t-test was larger than t-table, alternative hypothesis of this research was accepted and null hypothesis was rejected. It means that there was a significant effect of concept mapping strategy of the ability of the second year students of SMA PGRI Pekanbaru in writing explanation text.Key Words: Writing,Writing Ability, Concept Mapping Strategy, Explanation Text.